A Certified Health Physicist's Reflections on a 40-Year Career in Radiation Protection. Issue 4 (31st October 2016) - Miller, Mark L.
This is a reflection from a certified health physicist regarding his becoming aware, during his 40-year career, that the linear no-threshold (LNT) model and the associated As Low As Reasonably Achievable concept have no scientific basis and make no positive contribution to radiation safety. They should be replaced by an alternative, scientifically based model that includes a threshold, below which there is no harm, and recognition of hormesis and the adaptive response, which reflect the benefits of low-dose and low-dose-rate radiation exposure. Continued use of the unscientific LNT model is not conservative, as most regulators complacently claim but actually harmful. Examples of these harmful impacts in the areas of nuclear power, nuclear medicine, and environmental management are included.